An anatomical study of the proximal aspect of the medial femoral condyle to define the proximal-distal condylar length - Chia-Ming Chang; Wen-Tien Wu; Kuan-Lin Liu; Kuang-Ting Yeh; Cheng-Huan Peng; Ing-Ho Chen (Tzu Chi Medical Journal)
Objective: Despite its possible role in knee arthroplasty, the proximal-distal condylar length (PDCL) of the femur has never been reported in the literature. We conducted an anatomic study of the proximal aspect of the medial femoral condyle to propose a method for measuring the PDCL. Materials and Methods: Inspection of dried bone specimens was carried out to assure the most proximal condylar margin (MPCM) as the eligible starting point to measure the PDCL. Simulation surgery was performed on seven pairs of cadaveric knees to verify the clinical application of measuring the PDCL after locating the MPCM. Interobserver reliability of this procedure was also analyzed. Results: Observation of the bone specimens showed that the MPCM is a concavity formed by the junction of the distal end of the supracondylar ridge and the proximal margin of the medial condyle. This anatomically distinctive structure made the MPCM an unambiguous landmark. The cadaveric simulation surgical dissection demonstrated that the MPCM is easily accessed in a surgical setting, making the measurement of the PDCL plausible. The intraclass correlation coefficient was 0.78, indicating good interobserver reliability for this technique. Conclusion: This study has suggested that the PDCL can be measured based on the MPCM in a surgical setting. PDCL measurement might be useful in joint line position management, selection of femoral component sizes, and other applications related to the proximal-distal dimension of the knee. Further investigation is required.